Levels of Processing Affect Perceptual Features in Visual Associative Memory. (February 2021) - Ovalle-Fresa, Rebecca; Uslu, Arif Sinan; Rothen, Nicolas
The levels of processing (LOP) account has inspired thousands of studies with verbal material. The few studies investigating levels of processing with nonverbal stimuli used images with nameable objects that, like meaningful words, lend themselves to semantic processing. Thus, nothing is known about the effects of different levels of processing on basic visual perceptual features, such as color. Across four experiments, we tested 187 participants to investigate whether the LOP framework also applies to basic perceptual features in visual associative memory. For Experiments 1 and 2, we developed a paradigm to investigate recognition memory for associations of basic visual features. Participants had to memorize object–color associations (Experiment 1) and fractal–color associations (Experiment 2, to suppress verbalization). In Experiments 3 and 4, we extended our account to cued recall. All experiments revealed reliable LOP effects for basic perceptual features in visual associative memory. Our findings demonstrate that the LOP account is more universal than the current literature suggests.